Clinico-radiological findings of neuroendocrine tumour metastases to the orbit. (2nd January 2022) - Ryan, T G; Juniat, V; Stewart, C; Malhotra, R; Hardy, T G; McNab, A A; Davis, G; Selva, D
ABSTRACT: Purpose: We present the clinico-radiological findings of neuroendocrine tumour metastases to the orbit. Methods: This was a multicentre, retrospective study of patients with neuroendocrine tumour metastases to the orbit. Data was collected from medical records across five different sites within Australia and the United Kingdom. Results: Nine patients (eleven lesions) were identified. The most common presenting complaint was diplopia (5/9, 56%). Disease occurred bilaterally in two patients. Seven patients (78%) had extraocular muscle involvement. The lateral recti (4/9, 44%) and superior recti (2/9, 22%) were the most commonly affected. Ocular presentation preceded primary tumour diagnosis in three patients (33%). On orbital imaging, metastases were most commonly reported as well circumscribed, ovoid or round, heterogeneous, contrast-enhancing masses. Features of intralesional haemorrhage and bony invasion are uncommonly reported. Conclusions: Neuroendocrine tumour metastasis to the orbit is uncommon. Metastases have a propensity for the extraocular muscles, commonly presenting as heterogeneous, well circumscribed, contrast-enhancing lesions on neuroimaging. New ocular symptoms, a history of neuroendocrine tumours, and these radiological findings, should lead to high clinical suspicion of metastatic disease. Atypical findings warrant biopsy to exclude other causes of orbital lesions.